A novel statistical model assessing the self performance of knowledge management within SMEs in China - Ahmad, Othman; Yao, Liu; Omar, R. Mahdi; Jing, Wang (Elsevier Ltd, 2011)
Recently, the evaluation of knowledge management has become increasingly important. Nevertheless, few studies explicitly distinguished knowledge management self's performance from its effectiveness. This paper introduces a new evaluation model by partitioning the process of implementing knowledge management into three stages, including: 1) the external and internal environment analysis; 2) knowledge management activity planning; and 3) the knowledge management implementation decision making. Data is collected from Chinese small and medium sized enterprises by questionnaires and semi-structured interviews. The regression results prove that the three factors positively contribute to knowledge management self's performance with knowledge management activity planning impacts most and decision making less. Other useful factors are also indicated for enterprises to assess and predict their knowledge management self's performance.